Peran Pemerintah Desa Terhadap Swadaya Pengelolaan Limbah Industri Di Desa Sumberejo Kecamatan Pagak - Husnul Hakim; Arga Nurwahid; Eko Yusuf Wahyudi (Journal of Governance Innovation, 2025)
Industrial waste management at the village level is a complex issue that requires the involvement of various parties, including the village government, the community, and the industrial sector. This study aims to identify and analyze the role of the village government in supporting community self-reliance in industrial waste management in Sumberejo Village. Furthermore, this study explores the potential for establishing a waste bank as a sustainable solution to address waste problems in the village. Using a qualitative approach through interviews, observations, and document studies, this study found that the village government plays a facilitator in waste management, but still faces various challenges. The lack of specific regulations in the form of Village Regulations (Perdes), limited resources, and social resistance from the community are major obstacles to policy implementation. Furthermore, collaboration between the village government, academics, and the industrial sector is still suboptimal, resulting in underdevelopment of innovation in waste management. Therefore, more inclusive policies, clear regulatory support, and a collaborative approach involving various stakeholders are needed. With appropriate policies and active community participation, a more effective, environmentally friendly, and sustainable waste management system can be realized.